Competencies for sustainable financial and economic management: Their impact on human capital development and national security - Sydorchuk, Orystlava; Kharechko, Dmytro; Khomenko, Hanna; Akimova, Liudmуla; Kosarevych, Nazar; Akimov, Oleksandr (Edelweiss Applied Science and Technology, 2024)
The relevance of the study is determined by the orientation of modern society towards the strategy of sustainable development. The advent of the era of “globalization through sustainable development” is accompanied by the strengthening of “old” threats and the emergence of “new” ones. According to the article, the sustainability viewpoint systemically links the social, economic, and environmental domains into a dynamic, long-term view, which is the fundamental contribution of the perspective to the examination of security challenges. It also signifies a paradigm change in how public administration functions when analyzing security risks at the state and federal levels. Competences for sustainable financial and economic management are considered in frames of sustainable public management, implying, in particular, positive impact on human capital and contributing to national security through ESG paradigm implementation.